EFEKTIVITAS PERAN MEDIATOR DALAM MENYELESAIKAN PERSELISIHAN ANTARA PEKERJA DAN PEMBERI KERJA (STUDI KASUS PADA KANTOR DINAS TENAGA KERJA KOTA SORONG) - Tamunete, Maria; Murary, Weron; Morintoh, Raymond R (Ensiklopedia of Journal, 2024)
Abstract: The role of the mediator in resolving disputes between workers and employers at the Sorong City Manpower Office is carried out first by the Manpower Office or the appointed mediator team calling the parties to come to clarify the information of the problem and the next stage the mediator prepares the first mediation session schedule to negotiate the problem with the parties so that it can be resolved by deliberation and consensus,  Because the purpose of obtaining the effectiveness of the role of industrial relations mediators in resolving industrial relations disputes in Sorong City is with the obstacles experienced by industrial relations mediators in resolving industrial relations disputes at the Sorong City Manpower Office. The research method carried out by the author in conducting this research is qualitative research that is descriptive, where the author conducts an in-depth analysis of this problem, in this study the primary data source is obtained from information or data from interviews at the Sorong City Manpower Office, secondary data is used to support the primary data that has been obtained. The data analysis used is qualitative descriptive, which means that the author wants to describe or describe the situation that will be observed in the field in a more specific (special), transparent and in-depth manner and focus on data quality and provide a detailed, complete explanation. The role of industrial relations mediators in resolving industrial relations disputes is effective, as evidenced by the data on the number of industrial relations disputes recorded at the Sorong City Manpower Office. The number of industrial relations dispute cases in the form of employment termination disputes and conflicts of interest resolved with the final result of the collective agreement, is more than the number of unresolved industrial relations dispute cases in the form of trade union/labor union disputes. Industrial relations mediators in resolving industrial relations disputes at the Sorong City Manpower Office come from external inhibiting factors or obstacles that come from outside the process of resolving industrial relations disputes through mediation, namely in the form of intervention from outside parties such as workers involving NGOs or the DPRD. Obstacles that come from within or from within the dispute resolution process through mediation are in the form of problems from the disputing parties themselves and conflicts of interest between the industrial relations mediator and the Head of Industrial Relations.Keywords: Mediator, Dispute, Workers and Employers, Manpower Office